2018
DOI: 10.1016/j.nutres.2018.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Conflicting relationship between dietary intake and metabolic health in PTSD: A systematic review

Abstract: Posttraumatic stress disorder (PTSD) is a disabling psychological condition associated with significant physical comorbidities. There has been growing evidence to support the relationship between PTSD and cardiometabolic disease. Disordered eating behaviors often seen in people with PTSD symptoms may explain increased cardiometabolic risk. This systematic review aimed to assess the quality of evidence surrounding dietary intake of individuals with symptoms or a diagnosis of PTSD and their associated risk with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 58 publications
0
8
0
Order By: Relevance
“…Poor diet quality is a leading cause of cardiovascular and metabolic disease and disability (Lim et al, 2012). Outside the eating disorder research (e.g., binging as a form of emotional avoidance), the impact of PTSD on diet is a topic that has not been given the scientific or clinical attention it deserves (Theal et al, 2018). This gap in the scientific literature needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Poor diet quality is a leading cause of cardiovascular and metabolic disease and disability (Lim et al, 2012). Outside the eating disorder research (e.g., binging as a form of emotional avoidance), the impact of PTSD on diet is a topic that has not been given the scientific or clinical attention it deserves (Theal et al, 2018). This gap in the scientific literature needs to be addressed in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Although a recent literature review (Hall et al, 2015) and meta-analysis (van den Berk-Clark et al, 2018) noted that in general PTSD appears to be associated with poorer activity and diet in several studies, evidence is mixed and few studies looking at these associations have examined the role of depression, used rigorous objective measurement procedures, or applied longitudinal designs (Hall et al, 2015). Findings regarding associations with eating behaviors are especially limited and inconsistent (Theal et al, 2018), though some studies have found positive associations between PTSD and dietary intake (van den Berk-Clark et al, 2018). In addition to a need for more rigorous research on the association between PTSD and dietary behaviors, it is important to distinguish between dietary behavior types and whether some differentially affect the association of PTSD with CVD risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with PTSD often have elevated BMI, glucose, insulin, and creatinine, which may be associated with cardiometabolic dysfunction [30] (Figure 1). For example, macrophages accumulate inside adipose tissue during obesity/insulin resistance generating cytokines and adipokines that may lead to inflammation [72]. Hyperinsulinemia sensitizes adipose tissue to lipid synthesis, which is associated with increased activity of glucocorticoids [66].…”
Section: Metabolic Changes and Ptsdmentioning
confidence: 99%